2010
DOI: 10.4314/ejhd.v24i1.62949
|View full text |Cite
|
Sign up to set email alerts
|

Programmatic correlates of maternal healthcare seeking behaviors in Ethiopia

Abstract: Background: Considerable improvement in maternal healthcare use has been observed since the inception of the health extension program (HEP) in Ethiopia in 2003. Objective: This paper evaluates the influence of HEP outreach strategies on maternal healthcare use. Method: Cross-sectional survey of 2,916 women with children 0 to 11 months from Amhara, Oromiya, Southern Nations, Nationalities and People's, and Tigray regions, obtained between December 2008 and January 2009, were analyzed using regression models to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
18
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 9 publications
5
18
1
Order By: Relevance
“…This is consistent with different reports from Ethiopia [12,[15][16][17]. However, it was higher than the 34% of EDHS 2011 report [2].…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with different reports from Ethiopia [12,[15][16][17]. However, it was higher than the 34% of EDHS 2011 report [2].…”
Section: Discussionsupporting
confidence: 92%
“…This training, support and follow up may bring knowledge and skill development to the model and it made them practice health packages well compared to non model HHs [3]. Findings from previous studies [8,9] revealed that, model families have good utilization of maternal health services. Mothers utilizing those services are more likely to gain access to other preventive services which commonly target children under five year of age.…”
Section: Discussionmentioning
confidence: 99%
“…In 2009, a survey conducted in four regions of Ethiopia reported that only 9% of women were giving birth at institutions [20]. Other recent studies in different regions of the country supported the finding that there is very little improvement in having more institutional deliveries [21-26].…”
Section: Introductionmentioning
confidence: 99%